2022
DOI: 10.1002/smsc.202100116
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization as a Facile Strategy to Enhance Efficacy of Macrophage Membrane‐Coated Nanoparticles in Osteoarthritis

Abstract: Osteoarthritis (OA) is a chronic degenerative joint disorder associated with pain and inflammation, and is the leading cause of disability worldwide. Owing to the complexity of OA inflammation driven by a plethora of inflammatory cytokines, current specific anti‐cytokine therapies have not been successful. Among the immune cells implicated in OA inflammation, macrophages reportedly regulate OA inflammation via macrophage polarization. Given that pro‐inflammatory M1 and anti‐inflammatory M2 macrophages have opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Since macrophage polarization plays a fundamental role in OA progression and regeneration, many efforts have been made to explore novel specific targets to inhibit or slow the progression of OA. For instance, M2 macrophage membrane-coated nanoparticles (Au-M2 NPs), a unique drug platform, could be applied as a highly anti-inflammatory and specific polarize macrophages to M2 type and eventually alleviate OA inflammation as well as matrix degradation ( 52 ). On the other hand, investigating the underlying molecular pathology of OA is also a pivotal research direction for differential treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since macrophage polarization plays a fundamental role in OA progression and regeneration, many efforts have been made to explore novel specific targets to inhibit or slow the progression of OA. For instance, M2 macrophage membrane-coated nanoparticles (Au-M2 NPs), a unique drug platform, could be applied as a highly anti-inflammatory and specific polarize macrophages to M2 type and eventually alleviate OA inflammation as well as matrix degradation ( 52 ). On the other hand, investigating the underlying molecular pathology of OA is also a pivotal research direction for differential treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mechanism research of macrophages has also drawn many researchers' attention. For example, NO was found to induce apoptosis and proinflammatory cytokines secretion, while others reported that it could protect chondrocytes and attenuates macrophagemediated inflammation (49)(50)(51)(52)(53). Therefore, exploring the mechanisms underlying on the macrophage and OA progression.…”
Section: Future Research Trendsmentioning
confidence: 99%
“…Alleviating OA inflammation and matrix degradation 3. Enhanced therapeutic efficiency [ 144 ] Allergic asthma BMMs PLGA Dnmt3aos In vitro: M2 macrophage In vivo: allergic asthma mice 1. Ameliorate allergic asthma with a marked reduction of lung inflammation 2.…”
Section: Application Of Macrophage Membrane Biomimetic Nanoparticlesmentioning
confidence: 99%
“…The researchers revealed a promising therapeutic strategy to break a vicious and self-perpetuating cycle in OA patients. Teo et al purposed a facile strategy to improve the efficacy of the macrophage membrane-derived nanoparticles ( Teo et al, 2022 ). They prepared pro-inflammatory M1 and anti-inflammatory M2 macrophages through cell polarization, and then constructed M2 macrophage membrane-coated gold nanoparticles (Au-M2 NPs).…”
Section: Novel Nanotherapeutic Strategies For Oa Therapymentioning
confidence: 99%